Evaluation of the Ramadhan Safari Program to Improve the Social and Religious Values of FKS Ra'as - Nur Mahmudi Ismail; Muhammad Andi Syafruddin; Hendra Purwanto; Ahmad Zainullah (al-Afkar, Journal For Islamic Studies, 2024)
This study aims to evaluate the Safari Ramadhan program to increase social and religious values. This study uses a quantitative approach with a descriptive evaluation study type method. The data collection instrument used was interview. The technique used in sampling was random sampling with 3 organizers or respondents. This research was conducted to obtain data and generate conclusions in the field regarding the evaluation of the Ramadhan safari program, using the CIPP evaluation model (Context, Input, Process and Product). The results of this study indicate that the program carried out is in accordance with what was expected by the committee, with the large number of activity participants and enthusiastic support from the surrounding community in the area of ​​the activity so that social and religious values ​​in society can be felt by the santri and the surrounding community, Recommendations for development the next activity to develop more collaborative activities is even better, flyers or information through social media is further enhanced so that the scope can be expanded. The strategy carried out by the Santri Communication Forum (FKS) of Ra'as District, Sumenep Regency in internalizing social and religious values, based on the findings of researchers in the field, is to carry out program planning, approach members and provide examples. The results of internalizing social and religious values in improving the quality of members The Santri Communication Forum (FKS) means that members can understand and practice social and religious values, members get good grades, by internalizing the santri to have a religious character in terms of increasing their faith and devotion to Allah SWT.